Saccharomyces cerevisiae-Starmerella bacillaris strains interaction modulates chemical and volatile profile in red wine mixed fermentations. (August 2019) - Englezos, Vasileios; Pollon, Matteo; Rantsiou, Kalliopi; Ortiz-Julien, Anne; Botto, Riccardo; Río Segade, Susana; Giacosa, Simone; Rolle, Luca; Cocolin, Luca
Abstract: The use of Starmerella bacillaris in combination with Saccharomyces cerevisiae is considered as a state-of-the-art biological application to modulate wine composition. This application implies a detailed understanding of yeast-yeast interactions during mixed fermentations and their effect on the composition of the resulting wines. In this context, ten commercial S. cerevisiae strains were used as partners of an indigenous, previously characterized Starm. bacillaris strain in order to get a better insight into the impact of S. cerevisiae strain employed. The different combinations of strains tested influenced the growth dynamics, the fermentation behavior and, as a consequence, wine composition in a couple-dependent manner. In addition, wines produced from mixed fermentations had significantly lower levels of ethanol, acetic acid and ethyl acetate, and showed higher amounts of glycerol, higher alcohols and esters compared to pure S. cerevisiae control fermentations. This study reveals the importance of S. cerevisiae strain choice on the chemical composition of the wines produced from mixed culture fermentations with Starm. bacillaris . Graphical abstract: Unlabelled Image Highlights: Ten Saccharomyces cerevisiae strains were used as partners of Starmerella bacillaris . Combinations of strains tested influenced growth dynamics and wines composition. Mixed fermentation significantly decreased ethanol content. Mixed fermented wines showed higher concentrations of higher alcohols and esters.